Status and development for detection and control of ammonium bisulfate as a by-product of SCR denitrification - Kunling Jiao (Nature Portfolio, 2021)
Abstract When denitrification technology using NH3 or urea as the reducing agent is applied to remove NOx from the flue gas, ammonium bisulfate (ABS) by-product will also be generated in the flue gas. ABS has an impact on catalyst life span, denitrification efficiency etc., air preheater and its downstream thermal equipment also have a significant negative impact due to its plugging and corrosion. The requirement for NOx removal efficiency is improved by ultra-low emissions in China. However, wide-load denitrification makes the flue gas composition and temperature changing more complicated. Increasing ammonia injection can improve the NOx removal effect, but too much ammonia injection will lead to the formation of ABS and the increase of deposition risk, the contradiction between these two aspects is amplified by ultra-low emissions and wide-load denitrification in many plants. Coordinating NOx control and reducing the impact of ABS on equipment are issues that the industry needs to solve urgently. In recent years, extensive research on ABS had been carried out deeply, consequently, there has been a relatively in-deepth knowledge foundation for ABS formation, formation temperature, deposition temperature, dew point temperature, decomposition behavior, etc., but the existing researches are insufficient to support the problem of ABS under full load denitrification completely resolved. Therefore, some analysis and detection methods related to ABS are reviewed in this paper, and the impact of ABS on SCR, air preheater and other equipment and the existing research results on reducing the impact of ABS are summarized also. It is hoped that this review will provide a reference for the industry to solve the problems of ABS that hinder wide-load denitrification and affect ultra-low emissions.